2021
DOI: 10.1007/s40003-021-00563-x
|View full text |Cite
|
Sign up to set email alerts
|

Farmers Adoption Level of New Rice for Africa (NERICA) Varieties in Ekiti State, Nigeria

Abstract: New Rice for Africa (NERICA) varieties were developed at the Africa Rice Centre (WARDA) in 1990s, based on crossings between African rice (Oryza glaberrima Steud.) and Asian rice (O. sativa L.). Nigeria has been one of the seven West African countries that benefited from multinational NERICA rice disseminated project. The purpose of the study is to examine farmers' adoption level of NERICA rice varieties in Ekiti State Nigeria. Multistage sampling procedure was used in selecting ninety NERICA rice farmers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This reveals that the bulk of agricultural-related information such as sources of planting materials, input prices, crop varieties, modern agricultural production practices and technologies are made known to the farmers through agricultural extension services. Akinnagbe and Akinbobola (2022) found that extension agents are responsible for about 72.0% of the sources of information to farmers on NERICA rice varieties in Ekiti State. Maulu, et al (2021) reported that agricultural extension as a major source of information to farmers plays a significant role in disseminating research-based agricultural knowledge and technology to farmers.…”
Section: Sources Of Farm-related Information About Ayb Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reveals that the bulk of agricultural-related information such as sources of planting materials, input prices, crop varieties, modern agricultural production practices and technologies are made known to the farmers through agricultural extension services. Akinnagbe and Akinbobola (2022) found that extension agents are responsible for about 72.0% of the sources of information to farmers on NERICA rice varieties in Ekiti State. Maulu, et al (2021) reported that agricultural extension as a major source of information to farmers plays a significant role in disseminating research-based agricultural knowledge and technology to farmers.…”
Section: Sources Of Farm-related Information About Ayb Productionmentioning
confidence: 99%
“…in a study identified challenges confronting AYB farmers in southeast Nigeria as diseases and pests, unavailability of farm input, high labour cost, inadequate funds, lack of farm credit and literacy level of farmers which could be linked to their old age. According to the findings ofAkinnagbe and Akinbobola (2022) pest infestation, climate change and inadequate capital for adopting the technology are some of the challenges facing food crop farmers.…”
mentioning
confidence: 99%